Methodical Features of Teaching Homonyms of English Language Using Computer Technology - Madina Ashuraliyevna, Mamedova (International Journal of Psychosocial Rehabilitation, 2020)
The implementation of computer technology in the process of teaching English homonyms and their use are discussed in this article. At the implementation of multimedia and presentation in teaching English homonyms expand the range of opportunities of their mastering. The very understanding of the phenomenon of homonymy and its classical definition. Many scientists involved in the methodology of teaching foreign languages, rightly drew attention to the effectiveness of the game method with the use of a computer. This is due to the fact that the game manifests especially fully, and sometimes unexpectedly the ability of any person, and the learner, in particular.